Bioremediation of crude oil polluted seawater by a hydrocarbon-degrading bacterial strain immobilized on chitin and chitosan flakes - Gentili, Alejandro Raúl (2006)
In this laboratory-scale study, we examined the potential of chitin and chitosan flakes obtained from shrimp wastes as carrier material for a hydrocarbon-degrading bacterial strain. Flakes decontamination, immobilization conditions and the survival of the immobilized bacterial strain under different storage temperatures were evaluated. The potential of immobilized hydrocarbon-degrading bacterial strain for crude oil polluted seawater bioremediation was tested in seawater microcosms. In terms of removal percentage of crude oil after 15 days, the microcosms treated with the immobilized inoculants proved to be the most successful. The inoculants formulated with chitin and chitosan as carrier materials improved the survival and the activity of the immobilized strain. It is important to emphasize that the inoculants formulated with chitin showed the best performance during storage and seawater bioremediation.